Peran sustainability report, dewan Komisaris, Komisaris Independen, Komite Audit dan Spesialisasi Industri KAP terhadap audit report lag - Rosanita, Devi; Djaddang, Syahril; Mulyani, JMV. (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
Submission of Periodic Financial Reports of Issuers or Public Companies, the Financial Services Authority requires that every public company registered on the capital market must submit annual financial reports that have been audited by an independent auditor to the Financial Services Authority and announced to the public no later than the end of the fourth month after the year this is regulated in the Financial Services Authority Regulation Number: 7/POJK.04/2018 concerning Submission of Reports Through the Electronic Reporting System of Issuers or Public Companies. Companies that do not submit financial reports by the specified time limit will be subject to administrative sanctions. This study aims to determine the effect Good Corporate Governance namely the board of commissioners, independent commissioners, audit committee and Public accounting firm industry specialization audit report lag. the population in this study are manufacturing and mining companies listed on the IDX (Indonesian Stock Exchange) in 2021 period. There are 287 public companies listed on the Indonesia Stock Exchange which are registered as a population. Samples were selected using techniques purposive sampling, and a sample of 71 companies was obtained. This research model uses multiple regression analysis and moderation regression analysis or Moderated Regression Analysis (MRA). The results of the study show that independent commissioners and Public accounting firm industry specialization have no effect on audit report lag, so that the size of the independent commissioner and Public accounting firm industry specialization will not add to the time span audit report lag, the board of commissioners and the audit committee have an effect on audit report lag, so that the more members of the board of commissioners and the audit committee will reduce the term audit report lag. Sustainability report able to moderate the independent commissioner against audit report lag, until it gets bigger sustainability report it will strengthen the relationship of independent commissioners to audit report lag and independent commissioners can be more effective in supervising management and ensuring that the audit process is carried out properly and on time. Future research can add to research in other fields so that more samples are studied.